MURABAHAH PROVISION: THE KEY TO CLIENT-ORIENTED BUSINESS STRATEGIES AT BMT EL-MUHSIN - Mardianton, Mardianton; Efendi, Faisal; Hertasmaldi, Hertasmaldi; Mulyani, Ridha; Nurlaila, Nurlaila (IAIN Lhokseumawe, 2024)
The research objective of this paper is to examine the impact of murabahah financing and entrepreneurial spirit on the income of Baitul Mal wa Tamwil El-Muhsin customers. This quantitative study comprises two independent variables and one dependent variable. There are 1,085 customers in the population. The Cochran formula was employed to implement stratified random sampling. A total of 196 customers were chosen as samples. The data collection technique employs a questionnaire, while the data analysis technique on the impact of financing and entrepreneurial spirit on customer income employs path analysis. The F test results indicated that the entrepreneurs of BMT el-Muhsin Hall have a substantial impact on their souls, with a F count of 17,664. Despite the fact that the coefficient of the financing route has a significant partial influence on the soul of entrepreneurs at BMT el-muhsin Hall (T count = 4,203), the hypothesis is acceptable. Structural analysis 2 demonstrated that the revenue of BMT el-Muhsin Hall customers was significantly impacted by the financing of mortgages and the spirit of entrepreneurship, with a value of 73.10%. Although the analysis of the murabahah financing route has a partial influence of 69.00% on the soul of entrepreneurs and the coefficient of the spirit of enterprises has a significant influence on the income of the entrepreneur of 11.30%, thus, the hypothesis is accepted.